Knowledge Spillovers and Total Factor Productivity Across Countries: The Role of Institutions - Ali, Naveed; Rukh, Lala; Khan, Muhammad Imad; Khan, Sohrab (Pakistan Journal of Humanities and Social Sciences, 2023)
Why certain countries gain more than others from knowledge spillover is a topic of intense dispute in academic circles. It is generally believed that knowledge spillovers provide greater opportunities to countries to follow higher domestic productivity. However, some economies are not experiencing the productivity benefits of knowledge spillovers and implementing actions that would significantly move the economy onto a higher, more sustainable development path.This study examines the interaction between knowledge spillovers with institutional quality in affecting total factor productivity for sample countries. To serve this purpose, this study employs Cross Sectionally Augmented Autoregressive Distributive Lag (CS-ARDL) econometric technique. The results suggest that knowledge spillovers contributing to domestic productivity. However, the relationship between knowledge spillovers and domestic productivity depends on certain level of institutional characteristics. Hence, countries with high quality of institutions get more benefited from knowledge spillovers. Therefore, policy complementarity is pre-requisite for domestic productivity. The implication for policy sequencing is that the countries, where policy complementarities are weak, must have a strategy in place to improve their structural and institutional quality.